The Emergence of a New School: An Approach in the Light of Autonomy and Curricular Flexibility - Cristóvão, Natalina (2021)
In the 2017/2018 academic year, the Ministry of Education carried out an experimental project at national level, underOrder No. 5908/2017, called the Autonomy and Curricular Flexibility Project (PAFC). In the following year, with DecreeLaw No. 55/2018 of 6 July, it took the form of a regulated practice, whose framework challenges schools, giving themautonomy to carry out a flexible and contextualized management of the curriculum in articulation with the educationalcommunity in an interdisciplinary work perspective, in order to deepening, reinforcing and enriching Essential Learning.These guidelines place the curriculum in a project position that allows schools to manage and develop it in a way thatenables all students to achieve the skills foreseen in the Profile of Students Leaving Mandatory Schooling. Taking intoaccount what has been said above, it is our purpose to share the perceptions and practices of the artistic fields teachersthat integrate the teaching staff of the 1st CEB schools that joined the pilot project in six schools of the AutonomousRegion of Madeira.